RETRACTED: Estimation of the optimum tilt angle of solar collectors in Coatzacoalcos, Veracruz. (June 2020) - Herrera-Romero, J.V.; Colorado-Garrido, D.; Escalante Soberanis, M.A.; Flota-Bañuelos, M.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of Editor-in-Chief, because it contains a number of discrepancies such as: 1.Almost all numbers presented in the paper differ from reality by an order of magnitude of one million. 2.Although the paper is about the optimal angles for a specific location (Veracruz) only beam radiation is considered ignoring the diffuse and ground reflected components of radiation, which according to the specific weather conditions of a location can significantly affect the results. 3.No real weather data were used in the analysis which can lead to errors of the order of 30%. The Authors apologize for the inconvenience caused by these mistakes and agree with the retraction. The Journal apologizes that these errors were not detected during peer review.